2022
DOI: 10.3389/fmicb.2022.887136
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic and Microscopic Analysis of Magnetotactic Bacteria in Tangyin Hydrothermal Field of Okinawa Trough

Abstract: Magnetotactic bacteria (MTB) have been found in a wide variety of marine habitats, ranging from intertidal sediments to deep-sea seamounts. Deep-sea hydrothermal fields are rich in metal sulfides, which are suitable areas for the growth of MTB. However, MTB in hydrothermal fields have never been reported. Here, the presence of MTB in sediments from the Tangyin hydrothermal field was analyzed by 16S rRNA gene amplicon analysis, metagenomics, and transmission electron microscopy. Sequencing 16S rRNA gene yielded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Nowadays, customized VSM setups can achieve signal sensitivities ranging from 1 · 10 −5 to 1 · 10 −6 emu [ 17 ]. The employment of VSM has revealed the metagenomic analysis of magnetotactic bacteria [ 18 ], the detection of ferromagnetic materials in insect tissues responsible for their orientation toward external magnetic fields under both light and dark conditions [ 19 ], and the characterization of magnetic nanoparticles in the use of DNA isolation [ 20 ] or for hyperthermia therapies [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, customized VSM setups can achieve signal sensitivities ranging from 1 · 10 −5 to 1 · 10 −6 emu [ 17 ]. The employment of VSM has revealed the metagenomic analysis of magnetotactic bacteria [ 18 ], the detection of ferromagnetic materials in insect tissues responsible for their orientation toward external magnetic fields under both light and dark conditions [ 19 ], and the characterization of magnetic nanoparticles in the use of DNA isolation [ 20 ] or for hyperthermia therapies [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the unique physicochemical conditions associated with hydrothermal vent systems give rise to abundant microbial communities. For example, there are abundant magnetotactic bacteria, sulfur-oxidizing bacteria ( Sulfurimonas and Sulfurovum ), sulfate-reducing bacteria ( Thermosulfidibacter and Desulfothermus ) and methanogens ( Methanococcales and Methanosarcinales ) living in the hydrothermal vents [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. However, the interspecies relationship of microbial communities and their ecological function in hydrothermal vents from Okinawa Trough has been rarely studied.…”
Section: Introductionmentioning
confidence: 99%
“…In deep-sea sediments, magnetosomes have been observed with microbial cells (Liu et al, 2017 ; McGlynn et al, 2018 ; Cui et al, 2021 ), whereas magnetosomes have been observed without microbial cells (Dong et al, 2016 ; Yamazaki et al, 2019 ). Although the previous deep-sea studies attempted to clarify the taxonomy of MTB involved in the formation of magnetosomes by 16S rRNA gene sequences, metagenomic analysis was performed to characterize MTB, the presence of which has been demonstrated by electron microscopy in deep-sea hydrothermal sediments (Chen et al, 2022 ). However, their metagenomic approach was unsuccessful in revealing the taxonomic affiliations of magnetosome genes and their arrangement into MGCs.…”
Section: Introductionmentioning
confidence: 99%